High-dose chemotherapy followed by allogeneic stem cell transplantation in high-risk relapsed and refractory aggressive non-Hodgkin lymphoma: Results of a prospective study of the German high-grade non-Hodgkin lymphoma study group. - Bertram Glass; Justin Hasenkamp; Gerald Wulf; Peter Dreger; Michael Pfreundschuh; Martin Gramatzki; Gerda Silling; Christian Wilhelm; Matthias Zeis; Sebastian Pfeiffer; Lorenz Trümper; Norbert Schmitz (Journal of Clinical Oncology, 2012)
8004 Background: The role of allogeneic stem cell transplantation (alloSCT) in high-risk aggressive NHL is poorly defined; the role of graft-versus-lymphoma effect is unclear. Reduced intensity conditioning has shown limited efficacy in patients with refractory disease. Methods: Patients with primary refractory disease, early relapse ( grade I correlated with improved PFS (HR 0.45, p=0.0088). Patients with refractory disease or early relapse (n=60) experienced PFS at 3y of 33%. Conclusions: Lymphoma-debulking (high-dose) chemotherapy followed by alloSCT shows excellent results in heavily pretreated patients with early relapse or primary refractory aggressive lymphoma. There was evidence of graft-versus-lymphoma activity in this setting. For patients with a fully matched (10/10) related or unrelated donor the results compare favorably to autoSCT or alloSCT following reduced-intensity conditioning.